Efectos de Mesoscala del Temporal del 29 de Octubre al 3 de Noviembre de 1985 sobre Costa Rica. - Romell Galo, Edwin (1996)
The effects of mesoscale associated with the meteorological situation from 29 October to 3 November 1985, which caused a Temporal over Costa Rica, are analyzed. The interaction of an anamalous southwesterly flow in the lower troposphere with the orographic system of Costa Rica generated large amounts of rainfall and floods on the Pacific Watershed of Costa Rica. The mountains blockaded the upstream wind in the surface layer, producing return currents from the east in the lower branch of the circulation, contrary to the predominant synoptic flow. This originated mesoscale convergence fields. The maximum values of rainfall, which in some places reached the 300 mm in 24 hours, were produced by rains of convective type at the beginning of the temporal. Later on the rains were of a stratiform (continuous and moderate) type.